Mission, money, and membership: An institutional perspective on teacher preparation at new graduate schools of education - Cochran-Smith, Marilyn; Jewett Smith, Reid; Alexander, Jeremy (Education Policy Analysis Archives, 2022)
This article explores how teacher education operates within market-organized environments. We argue that the forces of the market have acted against institutional isomorphism in teacher education, as evidenced by the emergence of new graduate schools of education (nGSEs), which are a new population of teacher preparation providers. We suggest that nGSEs are animated by logics based on highly-specialized missions, alternative funding models, and membership in powerful networks that set this population apart from others within the organizational field of teacher education. We also argue that there is remarkable variation and diversification among nGSEs, which has resulted in highly specialized teacher preparation niches that distinguish each nGSE from other members within the same population through mission-specific branding, publicity, and funding, which in turn prompts increased demand for specialized programs. Finally, we suggest that although nGSEs have been shaped in many ways by the forces of the market, most of them are not completely dominated by market logics. Rather, most combine elements of the logic of markets with elements of other powerful logics, forming hybrids that create tensions, some of which are highly productive, prompting rapid organizational evolution, including name changes, reorganizations, and new partnerships.